Pengaruh Human Resource Management Practices pada Career Satisfaction dan Job Satisfaction terhadap Employees Turnover Intention di Rumah Sakit Gigi dan Mulut Pendidikan Universitas Trisakti - Erlyn Rahayu; Andreas Wahyu Gunawan P (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine and analyze the effect of Human Resource Management Practices on Employee Turnover Intention mediated by Job Satisfaction on employees at RSGM-P Trisakti University. The data collection technique used a questionnaire, The respondents of this study were 160 respondents are medical and non-medical employees who work at RSGM-P Trisakti University Jakarta, using the census method. The data analysis technique in this research uses SEM – PLS. The results of the analysis and discussion show that either directly or indirectly there is a positive and significant influence on Human Resource Management Practices on Employee Turnover Intentions mediated by Job Satisfaction on employees at RSGM-P Trisakti University. The implication for companies is support to pay attention to aspects of job satisfaction that are closely related to employee productivity such as Pay, promotion opportunities and facilities from the company, and pay attention to Compensation, Performance Appraisal, Promotion, Training & Development. This will further encourage employee engagement with work